2019
DOI: 10.1371/journal.pone.0224629
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in scientific production: A nationwide assessment among physicians in Peru

Abstract: ObjectiveTo determine the presence of a gender gap in the scientific production among Peruvian physicians and analyze either gap is associated with the presence of observable factors or the presence of prejudices against female physicians.MethodsWe analyzed data from the National Survey of User Satisfaction in Health 2016, a nationally representative survey that collected information about medical professionals working in health institutions in Peru. The outcome of interest was the number of publications in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
2
0
2
Order By: Relevance
“…Regarding financial policies for research, the study found that six policies have been implemented, including the funding of projects, special bonuses for research professors, and bonuses and/or publication aid. This result confirms the finding by Aguado-López and Becerril-García [ 19 ] that there is an insufficient allocation of state resources to research, which affects the promotion of research, with subsequent effects on infrastructure, financial support, and training [ 7 , 17 ]. This result calls for synergistic action by the state, companies, and society to implement a comprehensive sustainable development policy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding financial policies for research, the study found that six policies have been implemented, including the funding of projects, special bonuses for research professors, and bonuses and/or publication aid. This result confirms the finding by Aguado-López and Becerril-García [ 19 ] that there is an insufficient allocation of state resources to research, which affects the promotion of research, with subsequent effects on infrastructure, financial support, and training [ 7 , 17 ]. This result calls for synergistic action by the state, companies, and society to implement a comprehensive sustainable development policy.…”
Section: Discussionsupporting
confidence: 87%
“…In Latin American academic society, a multiplicity of tasks and commitments coexist in higher education institutions that require academics and scientists to establish collaborations and networks [ 15 ]. Research collaboration has contributed to generating international university networks through strategic alliances with prestigious entities [ 16 ], and these research networks have generated an increase in scientific production through coauthorship in publications [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…La selección para los cargos editoriales se hace entre quienes tienen mayores niveles académicos y ostentan cargos directivos en órganos de gobierno de universidades o instituciones científicas, por ello, el que haya menos mujeres con estas características explicaría esta desigualdad en la conformación de los comités editoriales 22 . A esto se debe sumar el histórico déficit de mujeres en algunas especialidades como urología y ortopedia 9 , aunque en las últimas décadas se ha comenzado a ver una tendencia creciente de participación femenina en otras especialidades como la anestesiología 10 .…”
Section: Discussionunclassified
“…Inequalities, based on an author's gender, have been systematically documented along different stages of the scientific publishing process (4,20). First, the proportion of women as first and senior authors in peer-reviewed publications is lower than expected given their prevalence in the field (4,20,(32)(33)(34)(35)(36)(37)(38)(39)(40). Moreover, across different fields, women tend to submit fewer papers than men (41), with larger imbalances in journals with higher impact factors (42).…”
Section: Introductionmentioning
confidence: 95%